[Retracted] The mathematical representation ability based on student's learning independence on problem based learning with scaffolding approach - Rosayanti, Salma Mauludyah; Mulyono, Mulyono (Department of Mathematics, Universitas Negeri Semarang, 2019)
The article has been retracted [THIS ARTICLE HAS BEEN RETRACTED] Following a rigorous, carefully concerns and considered review of the article published in Unnes Journal of Mathematics Education to article entitled â€œAThe mathematical representation ability based on student's learning independence on problem based learning with scaffolding approachâ€ Vol 8, No 2, pp. 105-110, August 2019, DOI: https://doi.org/10.15294/ujme.v8i2.32210. The document and its content has been removed from Unnes Journal of Mathematics Education, and reasonable effort should be made to remove all references to this article.